2010
DOI: 10.1519/jsc.0b013e3181d09eb3
|View full text |Cite
|
Sign up to set email alerts
|

Sport and Training Influence Bone and Body Composition in Women Collegiate Athletes

Abstract: This is a novel descriptive study to characterize off-season, preseason, and postseason bone and body composition measures in women collegiate athletes. From 2006 through 2008, 67 women collegiate athletes from 5 sports, softball (n = 17), basketball (n = 10), volleyball (n = 7), swimming (n = 16), and track jumpers and sprinters (n = 17) were scanned using dual energy X-ray absorptiometry (DXA) at 3 seasonal periods: (a) off-season = before preseason training, (b) preseason = after preseason training, and (c)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
67
7
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 13 publications
7
67
7
7
Order By: Relevance
“…We compared the expected difference due to growth in males and females with the observed change in LST over the season and the results pointed out that the observed increase was greater than the expected difference due to growth (males: 2.5 kg vs. 0.9 kg, p = 0.015; females: 1.5 kg vs. 0.07 kg, p = 0.009) which reinforces an effect of the training process in LST over the season. In addition to the findings previously mentioned in non-athletic pediatric subjects, it is important to address that our results extend the findings of other studies that followed young basketball players over a season, specifically the similar increases occurred in FFM (Siders et al 1991) and LST (Carbuhn et al 2010). In view of the aforementioned studies (Carbuhn et al 2010;Kim et al 2006;Molgaard and Michaelsen 1998;Siders et al 1991) it is likely that the effect of the training process greatly contributed to the observed increases in LST even though a potential effect of growth may have occurred, specifically in our male players.…”
Section: Discussionsupporting
confidence: 88%
“…We compared the expected difference due to growth in males and females with the observed change in LST over the season and the results pointed out that the observed increase was greater than the expected difference due to growth (males: 2.5 kg vs. 0.9 kg, p = 0.015; females: 1.5 kg vs. 0.07 kg, p = 0.009) which reinforces an effect of the training process in LST over the season. In addition to the findings previously mentioned in non-athletic pediatric subjects, it is important to address that our results extend the findings of other studies that followed young basketball players over a season, specifically the similar increases occurred in FFM (Siders et al 1991) and LST (Carbuhn et al 2010). In view of the aforementioned studies (Carbuhn et al 2010;Kim et al 2006;Molgaard and Michaelsen 1998;Siders et al 1991) it is likely that the effect of the training process greatly contributed to the observed increases in LST even though a potential effect of growth may have occurred, specifically in our male players.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, with respect to an optimum osteoanabolic exercise strategy, we would not advice to increase volumes of the given exercise type 3 further but to add new types of exercises in order to generate other types and distributions of strain and/or favorably impact the hormonal environment [33,34] and so additively/ synergistically enhance BMD. It is difficult to compare our results with data of available prospective physical activity or exercise studies [26,28,[35][36][37][38][39][40][41][42][43][44][45][46][47] that focus on BMD during young adulthood (17-30 years) due to the very dissimilar approach. The majority of studies either determined the effect of short, isolated, and specific exercise interventions on BMD [35, 39, 41, 43, 44, 46] 4 or accompany athletes of different disciplines (e.g., [36,37,40,45,47] in order to identify promising types of sports.…”
Section: Discussionmentioning
confidence: 95%
“…Physical activity is known to be a factor in promoting bone formation and moderate levels of physical activity, as little as twice per week, have been shown to reduce the risk of fractures [2]. Athletes, regardless of sport, have higher bone mineral density than non-athletes [3,[6][7][8], and BMD is higher in athletes engaged in high impact sports such as basketball and volleyball than in athletes in low-impact or non-impact sports such as swimming, water polo, and distance running [5][6][7][9][10][11][12]. Although sports with high-impact loading are associated with higher bone mineral density than low-impact or non-impact sports, confounding variables are differences in the athletes' body size and sport-specific training [11,13].…”
Section: Discussionmentioning
confidence: 99%
“…However, it has yet to be determined if any one sport or type of athletic activity is more beneficial or osteogenic than another. In general, research has shown that sports that have a repeated occurrence of high impact movements, such as gymnastics, volleyball, basketball, and track & field jumping events, have a greater effect on BMD when compared with sports with little or no impact such as cycling, water polo, and swimming [5][6][7][9][10][11][12].…”
mentioning
confidence: 99%